Diseño y construcción de un secador de granos con gas licuado de petróleo (GLP) para la asociación de cafeteros del cantón Yanzatza pertenecientes a APEOSAE; de un quintal de capacidad. - Ambrosi Robles, Vicente Roberto (2012)
This thesis work is based on the design and construction of a grain dryer with liquefied petroleum gas (LPG) for the association of coffee belonging to the canton Yanzatza APEOSAE, a 100 lb of capacity, "allowing to the association get a very handy machine which will solve the problems with the drying of coffee especially the high humidity in the area of weather conditions. The machine is an exposed motor, fan, control panel and some auxiliaries, features. The part calculation and elements which are part of the machine were developed through theory taken from books, literature professional support,equipment used in the drying of coffee,and our manager's cooperation. The selecction process of main parts was made which the best criteria in order to warranty a good perfomance, good design. The dryer's capacity is about 100 lb of drying, and 100 lb of pre drying, the percentage of final humidity in the coffe is 12% of humidity which is optimus to its storage